Banking Development, Economic Growth and Energy Consumption in Vietnam - Nguyen, Hong Anh Thi (International Journal of Energy Economics and Policy, 2020)
This study is aimed towards assessing the role of banking development and energy consumption on economic growth in Vietnam for the period ranging from 1990 to 2019. The researcher has collected data on the variables from 1990 to 2019 related with banking development, energy consumption and economic growth. On the data collected on the specified variables, certain tests have been conducted. This research has used Stata as the statistical platform to carry out data analysis where descriptive statistics, Augmented Dickey Fuller (ADF), Bounds test, and Autoregressive Distributed Lag Model (ARDL) have been applied on the data. The results indicated that the data was non-stationary and had trend which can predict the future data. Based on this condition, ARDL test and Bounds test were applied. The results indicated that overall, the model was found to be significant. Individually, energy consumption had a significant impact in both short term and long term however, there was insignificant association among banking development and economic growth. Keywords: Banking Development, Economic Growth, Energy Consumption, GDP, Vietnam JEL Classifications: Q1, O13 DOI: https://doi.org/10.32479/ijeep.10689